SOCIAL INTERPRETATION OF â€œWAJAH OTTâ€ IN POLITICAL COMMUNICATION MANAGEMENT CONTEXT OF PAUL RICOUER ANALYSIS (HAND CATCH OPERATION KPK -â€œOTTâ€™S FACEâ€) - Sumartias, Suwandi; Amina, Nurtyasih Wibawanti Ratna (Sinergi : Jurnal Ilmiah Ilmu Manajemen, 2018)
The writing purpose to understand and criticize Social Text "Facial OTT (The Face of Hand Catch Operation "KPK (Corruption Eradication Commission). Using research method â€œHermeneutic Analysis of Paul Ricouerâ€, it seeks to understand behind the text as representation andÂ  multi-interpretation. The results showed that two heads of areas whoseÂ  gotthe KPK â€˜s Hand Catch Operation (OTT), Jambi Governor and West Bandung Regent were "smiling" in front of journalistscoverage. Facial expression (non-verbal communication) of human has a very closely related with its attitude, thoughts and behavior. Body language (especially, facial expression) is an inseparable representation of what is in the mind and heart.Â  â€œWajah OTTâ€ as an important part of language, signs, and symbols and representations require fundamental and comprehensive interpretation. The social interpretation of the smiling of â€œOTT's faceâ€ is increasingly asserted as a representation of the existence of space-time, experience and reference (history) and culture of society, which are mutually related and inseparable. Recommendation, as long as we do not intend or dare to open the meaning behind the social "mask" on the text of "OTT's face" itself through understanding as "the way " and or the "being" of the whole human being as dasein (its history, ideals and habits), so corruption will forever be part of the culture of society.